Improving Biology Learning Outcomes on Enzymes and its Functions Through Modification of Multiple Refresentation Learning Model in Class XII IPA SMAN 1 Danau Panggang - Noraini Noraini (Edunesia: Jurnal Ilmiah Pendidikan, 2021)
The Biology learning process in class XII IPA at SMA Negeri 1 Danau Panggang has so far been more dominant in applying conventional learning models which are characterized by 1) teacher-centered, 2) emphasis on receiving knowledge, 3) less variety, 4) less empowerment of all potential students, and 5) using a monotonous method, because the teacher is dominant as the center of learning resources as a result, there are still many students who are passive, most students do not dare to ask questions. Student activity in learning and discussion is still low, many students in the learning process seem to be passive. As a result, learning becomes boring and less passionate, so learning outcomes are low. The purpose of this study was to improve learning outcomes of Biology on the subject of enzymes and their functions through Modification of the Multiple Representation Learning Model in class XII IPA SMAN 1 Danau Panggang. The research method used is comparative descriptive. Data were taken from 23 students with details of 8 men and 15 women. Then from the data, the percentage value of student learning completeness classically is sought using a predetermined formula using instruments in the form of observations of teacher activities, observations of student activities and student learning outcomes. The results of the final study showed that the average value obtained was 76.52 and the completeness of learning outcomes was 100%. Meanwhile, the activities of teachers and students also increased. Teacher activity increased from 59.72% to 79% with criteria from good to very good. Student activity also increased from 48% to 65% with good criteria